Performance of Hospitalists and Inpatient Clinical Outcomes. Issue 4 (2nd October 2018) - Kotala, Ragarupa; West, Daniel J.
Abstract: Use of the hospitalist model has reduced the number of primary care physicians taking care of inpatients. Physician shortages in primary care has forced many healthcare systems to use locum physicians as part of their delivery system and physician practice plan. With value-based purchasing and new payment models, measuring quality and patient-satisfaction with the hospitalist model is important. Hospital administrators need to carefully monitor the use of locum hospitalists, especially around quality of care and clinical outcomes.